Symptom clusters in patients with breast cancer receiving radiation therapy. (October 2019) - Chow, Selina; Wan, Bo Angela; Pidduck, William; Zhang, Liying; DeAngelis, Carlo; Chan, Stephanie; Yee, Caitlin; Drost, Leah; Leung, Eric; Sousa, Philomena; Lewis, Donna; Lam, Henry; et al.
Abstract: Purpose: Symptoms experienced by breast cancer patients often cluster together in groups known as "symptom clusters". The aim was to determine the symptom clusters in women with non-metastatic breast cancer treated by radiation therapy (RT). Methods: Edmonton Symptom Assessment Scale (ESAS) scores were taken from breast cancer patients receiving RT before, at completion of RT, and after RT. Exploratory factor analysis (EFA), principal component analysis (PCA), and hierarchical cluster analysis (HCA) were used to identify symptom clusters among the nine ESAS items at all three time points. Results: This study included 1224 patients. The PCA and EFA identified the same two symptom clusters before the start of RT: 1) pain, tiredness, nausea, drowsiness, appetite, and dyspnea; 2) depression, anxiety, and wellbeing. The HCA further split the symptoms into three clusters. Wellbeing, depression, and anxiety consistently clustered together. Among the ESAS scores collected at the end of and after RT, each statistical method identified different symptom clusters. For the symptom clusters experienced at the end of RT, the following symptoms were always in the same cluster: wellbeing, depression, and anxiety; nausea and appetite; drowsiness and dyspnea. Following RT, depression and anxiety consistently clustered together, with nausea and appetite in a second cluster. Conclusion: Among the symptom clusters derived before, at the end of RT, and after RT, the following symptoms consistently presented together: depression and anxiety, nausea and appetite, pain and tiredness, and drowsiness, dyspnea, and tiredness. Understanding symptom clusters in this population can improve management of symptoms. Highlights: Symptom clusters (SC) are symptoms experienced together, and are important in quality of life and symptom management. This study evaluated SD in 1224 metastatic breast cancer patients before, during and after receiving radiotherapy (RT). Two SC were found before the start of RT, with wellbeing, depression, and anxiety consistently clustered together. End of RT found clustering of: wellbeing, depression, anxiety; nausea appetite; drowsiness dyspnea. Following RT, depression and anxiety consistently clustered together, with nausea and appetite in a second cluster. Understanding the clustering of symptoms in this population can improve management of symptoms.